Effect of Production System (Barn and Free Range) and Slaughter Age on Some Production Traits of Guinea Fowl - Yamak, Umut Sami; Sarica, M.; Boz, M.A.; Uçar, A. (Oxford University Press, 2018)
A total of 200 Guinea fowl was reared in either barn or free-range systems and slaughtered at 14, 16, or 18 wk of age in order to determine the effects of production system on live weight, feed consumption, and some carcass and slaughter traits. Production system had a significant effect on live weight until 14 wk of age. Live weights were similar between free-range and indoor production systems at 16 (1, 150 g vs. 1, 152 g) and 18 (1, 196 g vs. 1, 203 g) wk of age. Guinea fowl reared in a free-range system consumed more feed (7, 693 g vs. 6, 983 g), and Guinea fowl reared in a barn had better feed conversion ratio (5.80 vs. 6.43) (P < 0.05). Production system, gender, and slaughter age did not affect the dressing percentage. Guinea fowl reared in a free-range system had significantly less abdominal fat (P < 0.05). © 2017 Poultry Science Association Inc.
Keywords: Carcass; Feed Consumption; Free-Range; Guinea Fowl; Slaughter